6=k-15

Simple and best practice solution for 6=k-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=k-15 equation:


Simplifying
6 = k + -15

Reorder the terms:
6 = -15 + k

Solving
6 = -15 + k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
6 + -1k = -15 + k + -1k

Combine like terms: k + -1k = 0
6 + -1k = -15 + 0
6 + -1k = -15

Add '-6' to each side of the equation.
6 + -6 + -1k = -15 + -6

Combine like terms: 6 + -6 = 0
0 + -1k = -15 + -6
-1k = -15 + -6

Combine like terms: -15 + -6 = -21
-1k = -21

Divide each side by '-1'.
k = 21

Simplifying
k = 21

See similar equations:

| 4=m-63 | | 7x-3=x+7 | | 12-(3x-6)-5(7-x)= | | 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 | | 71=-9n+8 | | 3*cos*2*x-5*cos*x-1=0 | | -3(y-2)=-5y+18 | | 7w-9=5(w+1) | | 7(y+6)-2y=2 | | 22-2x=14 | | .5x-2.4=.6 | | -4v+8(v-2)=-4 | | -3(4t-3)+5t=6t-5 | | 48+x(9+3)=288 | | 7u+5=5 | | -4v+8(v+2)=-4 | | 8g-7=-39 | | 3y+2f-f+1-3y+7=32 | | 2k+5=3 | | -5n+3=-4n-4 | | -6=-6w+4(w+3) | | 4b^2-169y^2= | | 9x+3x=10101010101001101 | | c+bc-11c-4=13c+4-2 |

Equations solver categories